2021
DOI: 10.3390/polym13203582
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Aqueous Sodium Alginate Slurries for LTO Battery Electrodes

Abstract: Rheological properties of electrode slurries have been intensively studied for manifold different combinations of active materials and binders. Standardly, solvent-based systems are under use, but a trend towards water-based electrode manufacturing is becoming more and more important. The different solvent is beneficial in terms of sustainability and process safety but is also accompanied by some disadvantages such as extraction of residual humidity and a higher complexity concerning slurry stability. Li4Ti5O1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…As is known, drilling uids are commonly designed as non-Newtonian uids and shear-thinning behavior is a notable viscosity characteristic of polymer containing suspensions. 45 It can be observed that the rheology of SA/BF closely followed shear-thinning behavior in a range of shear rates from 5.11 to 1022 s −1 , exhibiting high viscosity to suspend cuttings at low shear rates but low viscosity to reduce ow resistance at high shear rates. Meanwhile, one can see that shear thinning behavior is more obvious with increasing concentrations of SA.…”
Section: Herschel-bulkley Modelmentioning
confidence: 75%
See 1 more Smart Citation
“…As is known, drilling uids are commonly designed as non-Newtonian uids and shear-thinning behavior is a notable viscosity characteristic of polymer containing suspensions. 45 It can be observed that the rheology of SA/BF closely followed shear-thinning behavior in a range of shear rates from 5.11 to 1022 s −1 , exhibiting high viscosity to suspend cuttings at low shear rates but low viscosity to reduce ow resistance at high shear rates. Meanwhile, one can see that shear thinning behavior is more obvious with increasing concentrations of SA.…”
Section: Herschel-bulkley Modelmentioning
confidence: 75%
“…40,41 Moreover, the high solubility, tailorable rheological properties, excellent occulability and adsorption characteristic of sodium alginate account for its application in gel formation to enhance hydrogel strength. 42,43 Meanwhile, owing to the spatial network structure of SA in water, 44,45 its thixotropy and unique shear-thinning behavior make it an alternative additive that could be used in drilling uid. While there is a vast amount of bibliographic literature regarding the application of SA, salt-tolerant rheological and ltration loss properties in water-based drilling uid have not been reported; although it has been combined with graphene oxide to reduce the ltration loss, the detailed mechanism has not been systematically analysed.…”
Section: Introductionmentioning
confidence: 99%
“…[45,46] This enables the I units to act as dispersants, effectively preventing the aggregation of NCM and conductive carbon particles, thereby achieving a highly dispersed electrode. [47] Another benefit of the perfluoroalkyl moieties is the promotion of Liion diffusion, potentially enhancing the ion-conduction through binders. [48] Note that imide linkage was employed to connect the norbornene backbone and perfluoroalkyl moiety due to its excellent electro-chemo-mechanical stability.…”
Section: Design and Synthesis Of Pnci# Binder Systemmentioning
confidence: 99%
“…The results are very similar to those reported in Figure 7b, even if the capacity and coulombic efficiency data are more scattered, evidencing that the addition of EDC in the slurry produces the best electrodes. Keeping in mind that the capacitive and faradaic charge/discharge processes affect the electrode structure in different ways, it cannot be excluded that the optimization of the crosslinking conditions, with the addition of surfactants to decrease particle aggregation [36] and improve the slurry viscosity, can eventually increase the stability of NTP and LFP electrodes.…”
Section: Electrode Preparation and Characterizationmentioning
confidence: 99%